Flow Analysis In Pump As Turbines (PATs) Using Ansys Fluent Software - Engkos Koswara; Haris Budiman; Nur Fikri (University of Muhammadiyah Jakarta, 2020)
Pump As Turbines (PATs) is a small-scale power plant that uses hydropower as its driving force. The working principle is given the flow of water from a certain height into the pump output to produce pressure at the tip of the impeller blade and will rotate the impeller blades. In this research will be an optimization of Pump As Turbines (PATs) by changing the angle of the impeller blade tip to get the optimum design of Pump As Turbines (PATs) using Ansys fluent software. In using angle tip impeller blade 600, 450, 350, 300, and 250, pressure tip impeller blade the lowest on angle tip impeller blade 600 using incoming pressure 7 psi (0.483 bar) with a pressure value tip impeller blade 0.123 bar and the biggest one is angle tip impeller blade 250 using incoming pressure 14 psi (0.965 bar) with a pressure value tip impeller blade 0.543 bar. Based on the results of the impeller blade tip pressure obtained the optimal design of Pump As Turbines (PATs) is angle tip impeller blade 250 because of the critical angle of Pump As Turbines (PATs) if you use an impeller design less than 250 then the impeller blades will run out so that it can affect the resulting rotation.